Forest coffee certification in Ethiopia: Economic boon or ecological bane? - Till Stellmacher; Ulrike Grote (University of Bonn, Center for Development Research (ZEF), 2011)
The montane rainforests of Ethiopia are the worldwide origin of the Coffea arabica gene-pool. However, the forests witness high rates of depletion and deforestation leading to an irreversible loss of the forest ecosystem and biodiversity. Certification of forest coffee started in Ethiopia in 2002 with the aim to conserve the coffee forests and provide the peasants with a better livelihood. This paper evaluates the forest coffee production and the related human encroachment in the forests ecosystem in certified and non-certified cooperatives and explores the benefits of certification for the producers. The findings of the paper base on interviews conducted with forest coffee producers in nine certified and non-certified coffee cooperatives in the Kaffa Zone and Bench-Maji Zone of South-western Ethiopia and other stakeholders concerned. Empirical data shows that farmers undertake considerable interventions in the forest ecosystem in order to increase their coffee yields, e.g. by removing the forests' undergrowth and cutting trees. This promotes the degradation of the forest ecosystem and biodiversity and occurs irrespective of certification. Simultaneously, the local producer prices tripled in the same period - following the world market trend. This price increase has been found to be the main incentive for producers to intensify their production. This opens a conceptual dilemma for certification: certification aims at paying higher producer prices, but higher prices encourage the farmers to intensify their production and therewith to contribute to the process of forest depletion and loss of biodiversity. Empirical data also illustrate practical difficulties of certification. For the season concerned, some cooperatives did not pay significantly higher producer prices than non-certified cooperatives. Additionally, certification is not actively promoted nor understood by those who are certified. None of the interviewed member of certified cooperatives could give a reasonable answer to the question what certification actually is or means.
Keywords: 330; Certification; Coffee; Forest; Ethiopia